Marketing Practices of Some Selected Soft Drinks Industries in Bangladesh - Khatun, Mosa. Shely (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The study is usually descriptive. The paper's primary purpose is to understand the componential strategies and determinants of marketing in chosen soft drinks companies. The research's approach mainly based on primary data, although the full fledge of the study bear the assessment of secondary data-the consideration of two prominent companies that have been selected judiciously. The descriptive character shapes the research to constitute a congenial appropriation of analysis. Found that, the kind and other characteristics connected to the regional consumer quality are evaluated for developing the strategy. The companies should decrease pricing to balance the price and qualities of beverages with manufacturing alcohol-free soft drinks since most consumers are cautious about their health. The companies need to comply with stringent water quality requirements to allow dissolved solids, alkalinity and chlorides.